The association of parent’s outcome expectations for child TV viewing with parenting practices and child TV viewing: an examination using path analysis - Johnson, Lauren (Int J Behav Nutr Phys Act, 2015)
BACKGROUND: Television (TV) viewing has been associated with many undesirable outcomes for children, such as increased risk of obesity, but TV viewing can also have benefits. Although restrictive parenting practices are effective in reducing children’s TV viewing, not all parents use them and it is currently unclear why. The current study examined parenting practices related to TV viewing in the context of social- cognitive theory. Specifically, we hypothesized that positive and negative Parental Outcome Expectations for child’s TV Viewing (POETV) would be associated with social co-viewing and restrictive parenting practices, and that POETV and parenting practices influence the amount of TV viewed by child. METHOD: Data were collected from an internet survey of 287 multi-ethnic parents and their 6–12 year old children on participants’ sociodemographic information, parenting practices related to TV use, POETV, and parent and child TV viewing. Path analysis was used to examine the relationship amongst variables in separate models for weekday and weekend TV viewing. controlling for child age, household education, and parental TV viewing. RESULTS: The results provided partial support for the hypotheses, with notable differences between weekday and weekend viewing. The models explained 13.6 % and 23.4 % of the variance in children’s TV viewing on weekdays and weekends respectively. Neither positive nor negative POETV were associated with restrictive TV parenting in either model. One subscale each from positive and negative POETV were associated with social co-viewing parenting on both weekends and weekdays in the expected direction. Restrictive parenting practices were directly negatively associated with children’s TV viewing on weekdays, but not weekends. Social co-viewing parenting was directly positively associated with children’s TV viewing on weekends, but not weekdays. The strongest influence on children’s TV viewing was having a TV in the child’s bedroom. Negative POETV was weakly associated with having a TV in the child’s room. CONCLUSIONS: These findings suggest that POETV and parenting may have a greater impact on weekend TV viewing, when children tend to watch more TV, than weekday. The models suggest that POETV, parenting and especially removing the TV from children’s rooms may be promising targets for interventions.